Writing Namibia: Literature in Transition - Vale, Helen; Krishnamurthy, Sarala (Book collections on Project MUSE., 2018)
Writing Namibia: Literature in Transition is a cornucopia of extraordinary and fascinating material which will be a rich resource for students, teachers and readers interested in Namibia. The text is wide ranging, defining literature in its broadest terms. In its multifaceted approach, the book covers many genres traditionally outside academic literary discourse and debate. The 22 chapters cover literature of all categories in Namibia since independence: written and performance poetry, praise poetry, Oshiwambo orature, drama, novels, autobiography, women's writing, subaltern studies, literature in German, Ju'hoansi and Otjiherero, children's literature, Afrikaans fiction, story-telling through film, publishing, and the interface between literature and society. The inclusive approach is the book's strength as it allows a wide range of subjects to be addressed, including those around gender, race and orature which have been conventionally silenced.